A case report of Emergomyces orientalis infection in the lung of HIV infected in patient and literature review - Lifeng Luo; Ying Guo; Zunzhen Nie (Frontiers in Medicine, 2026)
Objective This study reports a rare case of pulmonary Emergomyces orientalis infection with clinical characteristics, diagnostic approaches and therapeutic regimens of this rare fungal infection, aiming to provide evidence for clinical diagnosis and management. Methods We retrospectively analyzed the patient’s clinical symptoms, imaging manifestations, laboratory examinations including metagenomic next-generation sequencing (mNGS), diagnostic and therapeutic procedures, as well as prognosis. Related published literature was searched, reviewed and summarized. Results The patient presented with a 3-day cough and expectoration. Conventional pathogen examinations showed the patient is infected with the HIV virus and definite diagnosis of Emergomyces orientalis infection was finally confirmed by mNGS of lung biopsy specimens. He received liposomal amphotericin B combined with symptomatic supportive therapy. Clinical symptoms were alleviated and pulmonary lesions were absorbed after treatment. Conclusion Pulmonary Emergomyces orientalis infection is uncommon and prone to missed diagnosis and misdiagnosis with high mortality. Routine pathogen culture yields a low positive rate. mNGS serves as a critical tool for early and accurate diagnosis. Individualized antifungal treatment, strict drug interaction assessment and therapeutic monitoring are essential to optimize clinical prognosis.